2018
DOI: 10.1111/cen.13542
|View full text |Cite
|
Sign up to set email alerts
|

In women with PCOS, waist circumference is a better surrogate of glucose and lipid metabolism than disease status per se

Abstract: Some cardiometabolic abnormalities in PCOS are related to central obesity, and following adjustment for WC does not differ from normal subjects. Waist circumference measurement has potential to take precedence over PCOS status as part of the assessment of cardiometabolic risk in reproductive-age women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
3
5
0
Order By: Relevance
“…In our study, although the mean age and BMI were comparable in the PCOS and control groups, the mean WC and WHR of the PCOS group were higher than those of the control group, which was consistent with previous studies [23,24]. Moreover, high levels of PINS, TG, and UA, and lower levels of HDL-C were observed in the PCOS group, which was in line with previous studies, showing that patients with PCOS have worse metabolic status than controls [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, although the mean age and BMI were comparable in the PCOS and control groups, the mean WC and WHR of the PCOS group were higher than those of the control group, which was consistent with previous studies [23,24]. Moreover, high levels of PINS, TG, and UA, and lower levels of HDL-C were observed in the PCOS group, which was in line with previous studies, showing that patients with PCOS have worse metabolic status than controls [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…No decisive proofs in the form of significant changes of BMI, waist circumference or percentage content of adipose tissue were found. This is significant in the light of the studies conducted by Pazderska et al, which indicate that waist circumference in patients with PCOS is suggested as a predictor of glucose and lipid metabolism disorders [45]. In the review of 10 studies performed by Pitter [46], a significant differential effect to the benefit of CrP was indicated; however, the clinical significance of this effect is still disputed.…”
Section: Resultsmentioning
confidence: 99%
“…22 We have recently shown that those with raised AMH have up to 4fold increased risk of having PCOS. 6,23 Waist circumference, a measure of central adiposity, is a marker of severity of PCOS and has been suggested to be a better surrogate of glucose and lipid metabolism in PCOS than the disease status per se. 9 The associations of FAI and waist circumference with PCOS are well-documented in the literature.…”
Section: P-value * Median (Iqr) Median (Iqr)mentioning
confidence: 99%
“…8 It has also been suggested that serum AMH reflects ovarian size in PCOS patients and can be used as surrogate for transvaginal ultrasound in the diagnosis of PCOS. 23 Menstrual dysfunction is a common symptom in PCOS and is a consequence of anovulation. 6,23 Waist circumference, a measure of central adiposity, is a marker of severity of PCOS and has been suggested to be a better surrogate of glucose and lipid metabolism in PCOS than the disease status per se.…”
Section: P-value * Median (Iqr) Median (Iqr)mentioning
confidence: 99%
See 1 more Smart Citation